LEGAL PROTECTION OF THE RIGHTS AND OBLIGATIONS OF ONLINE OJEK DRIVERS BASED ON PARTNERSHIP AGREEMENTS IN TERMS OF INDONESIAN POSITIVE LAW - Muljanto Muljanto; Gindo L. Tobing; Wiwik Sri Widiarty (Sean Institute, 2023)
The online motorcycle taxi phenomenon is one of many changes or evolutions that take advantage of technology. So the legal protection of the rights and obligations of online motorcycle taxi drivers is very important to study, both regarding the governing legal rules and legal protection. In this study, 2 (two) problems were determined that had to be answered, namely how are the legal rules governing the rights and obligations of an online motorcycle taxi driver in Indonesia, and how is the legal protection of the rights and obligations of online motorcycle taxi drivers based on a Partnership Agreement in terms of Indonesian Positive Law. Based on the study results, the legal rules governing the rights and obligations of online motorcycle taxi drivers in Indonesia need to be revised, starting from the transportation ministry regulations and the rules in the partnership agreement. So that the legal protection of the rights and obligations of online motorcycle taxi drivers could be better. So that the effort that will be made is for the Government, as the party that must protect online motorcycle taxi drivers, to take concrete steps, namely issuing policies so that online motorcycle taxi drivers are not based on a Partnership Agreement but are included in the realm of Law Number 13 of 2003 concerning Manpower., renegotiating the contents of the Partnership Agreement which were very arrogant and detrimental to online motorcycle taxi drivers who are also part of Indonesian citizens, and taking steps to have online motorcycle taxi drivers appointed as employees.